Series Solutions
Additional Examples
STEP 1: Plug in $\displaystyle y(x) = \sum_{n=0}^{\infty}a_n x^n $ and compute all the different terms in the equation $$ \begin{align} (6x + 5)y &= \sum_{ n = 0 }^{ \infty }\,6 a_{ n } x^{ n+1 } + \sum_{ n = 0 }^{ \infty }\,5 a_{ n } x^{ n }\\ (-6x^2 - 2)y' &= \sum_{ n = 1 }^{ \infty }\,-6n a_{ n } x^{ n+1 } + \sum_{ n = 1 }^{ \infty }\,-2n a_{ n } x^{ n-1 }\\ 2y'' &= \sum_{ n = 2 }^{ \infty }\,2n(n-1) a_{ n } x^{ n-2 } \end{align} $$ STEP 2: Make the substitutions $ k = n-2 $, $ j = n-1 $ and $ p = n+1 $ to make all terms of the form $ x^{\text{index}} $ rather than the $ x^{\text{index}-1} $ or $ x^{\text{index}+2} $ or whatever. $$ \begin{align} (6x + 5)y&= \sum_{ p = 1 }^{ \infty }\,6 a_{ p-1 } x^{ p } + \sum_{ n = 0 }^{ \infty }\,5 a_{ n } x^{ n }\\ (-6x^2 - 2)y'&= \sum_{ p = 2 }^{ \infty }\,-6(p-1) a_{ p-1 } x^{ p } + \sum_{ j = 0 }^{ \infty }\,-2(j+1) a_{ j+1 } x^{ j }\\ 2y''&= \sum_{ k = 0 }^{ \infty }\,2(k+2)(k+1) a_{ k+2 } x^{ k }\end{align} $$ STEP 3: Change all the indices to the same letter (I use $ m $) and plug into the equation. $$ \begin{align} 2y'' + (-6x^2 - 2)y' + (6x + 5)y &= \sum_{ m = 0 }^{ \infty }\,2(m+2)(m+1) a_{ m+2 } x^{ m } \\ &+ \sum_{ m = 2 }^{ \infty }\,-6(m-1) a_{ m-1 } x^{ m } + \sum_{ m = 0 }^{ \infty }\,-2(m+1) a_{ m+1 } x^{ m } \\ &+ \sum_{ m = 1 }^{ \infty }\,6 a_{ m-1 } x^{ m } + \sum_{ m = 0 }^{ \infty }\,5 a_{ m } x^{ m } \end{align} $$ STEP 4: Collect like terms. $$ \begin{align} &(4a_2 - 2a_1 + 5a_0) + (12a_{3} - 4a_{2} + 5a_{1} + 6a_{0})x \\ &+ \sum_{ m = 2 }^{ \infty }\,(2(m+2)(m+1)a_{m+2} - 2(m+1)a_{m+1} - 6(m-1)a_{m-1} + 5a_m + 6a_{m-1})x^m = 0 \end{align} $$ STEP 5: Equate coefficients to 0.
Equating the constant term to 0 we get $$ a_2 = \frac{2a_1 - 5a_0}{4} $$ Equating the linear term to 0 we get $$ a_3 = \frac{4a_2 - 5a_1 - 6a_0}{12} $$ Finally, equating the general term to 0, we find that for $ m \ge 2,$ $$ a_{m+2} = \frac{2(m+1)a_{m+1} - 5a_m - (-6(m-1)a_m + 6a_m)a_{m-1}}{2(m+2)(m+1)} $$ STEP 6: We know that $ a_0 = y(0) = 2 $ and $ a_1 = y'(0) = 4.$ We then plug these values into the formulas found in step 5 to compute the coefficients of the solution.
From the equation for the constant term we get $$ a_2 = \frac{2(4) - 5(2)}{4} = -1/2 $$ From the equation for the linear term we get $$ a_3 = \frac{4(-1/2) - 5(4) - 6(2)}{12} = -17/6 $$ Finally, using the recurrence equation with $ m = 2 $ we get $$ a_4 = \frac{2(2+1)(-17/6) - 5(-1/2) - (-6(2-1)(-1/2) + 6(-1/2))(4)}{2(4)(3)} = -29/48 $$
So our solution is $$ y(x) = 2 + 4x - (1/2)x^2 - (17/6)x^3 - (29/48)x^4 + \cdots $$
You may reload this page to generate additional examples.If you have any problems with this page, please contact bennett@math.ksu.edu.
©2010, 2014 Andrew G. Bennett